Zona Franca de Manaus: uma análise comparativa entre seus decretos e os impactos socioeconômicos (1957 a 2019) - Calegare, Juliana Maria (Universidade Federal de São Carlos, 2021)
This paper aims to understand the operation and objectives of a free trade zone, as well as to understand whether the Manaus Free Trade Zone, created in 1957, meets the main purposes stipulated by law. The central idea is to develop an analysis that evaluates whether the objectives with the implementation of the FTZ were met, from the joint analysis of the determining decrees of the ZFM, and results present in economic and social indices. Thus, with the confrontation between desires and impacts, the effectiveness of the free zone model in the state is evaluated. From this analysis we conclude the importance of the pole in improving the lives of the population, especially in aspects related to education, income, work, development of industries and technology.
Manaus Free Zone: a comparative analysis between its decrees and socio-economic impacts (1957 to 2019)
Keywords: Zona Franca; Indústria; Impacto; Desenvolvimento socioeconômico; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::CRESCIMENTO, FLUTUACOES E PLANEJAMENTO ECONOMICO::CRESCIMENTO E DESENVOLVIMENTO ECONOMICO